Relationship Between Age and Education of Women of Fertile Age with Participation in Long-Term Contraceptive Methods - Erna Amin; Ajeng Hayuning Tiyas; Yulianti Anwar; Suryanti S; Nur Anita (Genius Journal, 2024)
Objective: The aim of this research is to determine the relationship between age and education and the decision of women of childbearing age (WUS) to become MKJP family planning acceptors in Mamuju District. Method: This research is quantitative research with a cross-sectional method. Data collection techniques include questionnaires. The data analysis used was univariate analysis and bivariate analysis with the chi square statistical test. Result: The results of research based on the Chi Square Test show that there is a relationship between age (p value = 0.050) and education (p value = 0.017) and MKJP family planning participation. Conclusion: The results of this study explain that there is a relationship between age, education, and WUS participation in family planning programs using long-term contraceptive methods.